Duinesian Elegies - Maria Rilke, Rainer (UNC Studies in the Germanic Languages and Literatures, 1975)
A poetic English rendering of Rainer Maria Rilke's "Duineser Elegien" printed together with the original German on facing pages. The translation places high value on conveying the meaning of the Elegies, although it does not attempt to retain the original meter. An additional, detailed interpretive commentary will increase the English-speaking reader's understanding of Rilke's complex poetry.